Interplay of serum taurine, S-adenosylmethionine, and cysteine levels in cancer risk: a prospective study - Liu, Chenan; Liu, Tong; Wei, Yaping; Shi, Jinyu; Deng, Li; Song, Mengmeng; Shi, Hanping (Frontiers in Pharmacology, 2024)
BackgroundAmino acids are known to play critical roles in cancer metabolism and progression. Among them, taurine, S-adenosylmethionine (SAM), and cysteine have garnered particular attention due to their interconnected metabolic pathways. This study sought to explore the associations between serum levels of these amino acids and cancer risk within Chinese adults.MethodsA nested case-control study was conducted within the China H-Type Hypertension Registry Study cohort, comprising 1,391 cancer cases and 1,391 matched controls. Serum concentrations of taurine, SAM, and cysteine were quantified, and their associations with cancer risk were evaluated using conditional logistic regression and Bayesian Kernel Machine Regression (BKMR) models.ResultsA total of 1,391 pairs of participants were included in this study. Their average age was 69.3 years ± 7.77 years, and 56% were male. Higher serum taurine levels were associated with a reduced risk of overall cancer. In contrast, elevated serum SAM levels were linked to an increased risk of digestive cancers. The BKMR model identified complex interactions among these amino acids and showed a significant overall negative association between the combined effect of taurine, SAM, and cysteine and cancer risk.ConclusionSerum taurine levels may offer protective benefits against cancer, particularly for digestive cancers, while its metabolites do not have such significant benefits. The intricate interactions among taurine, SAM, and cysteine underscore the need for a comprehensive approach to understanding their roles in the metabolic processes that drive tumorigenesis.Clinical Trial Registrationhttps://www.chictr.org.cn/showproj.html?proj=28262, identifier ChiCTR1800017274.